2020
DOI: 10.26803/ijlter.19.3.16
|View full text |Cite
|
Sign up to set email alerts
|

ESP Course Delivered to Personnel Working in Shifts for the State Emergency Service of Ukraine through a Student-Tailored Model

Abstract: The purpose of this research was to identify whether there had been an enhancement in students' language skills and perception of the ESP course if it had been delivered through a blended mode studenttailored model. The latter was aimed at training each English language skill separately. Reading and listening skills were trained online, the writing was taught both online and offline, and speaking was trained offline using speaking clubs that were held once a week. The TUTORROOM system was programmed to deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…) andDichek et al (2021), who argued that students who develop critical thinking have better learning outcomes. They are consistent with the results ofGiraldo-García et al (2015),Gökçearslan et al (2019),Lychuk et al (2021),Nozhovnik and Shykhnenko (2020),Schindler et al (2017), who found that the use of technology increases students' motivation, provides individualization of learning, improves their time management skills and overall learning satisfaction. The results of the study deepen the provisions introduced byDehghani et al (2011), Lin et al (…”
supporting
confidence: 91%
See 2 more Smart Citations
“…) andDichek et al (2021), who argued that students who develop critical thinking have better learning outcomes. They are consistent with the results ofGiraldo-García et al (2015),Gökçearslan et al (2019),Lychuk et al (2021),Nozhovnik and Shykhnenko (2020),Schindler et al (2017), who found that the use of technology increases students' motivation, provides individualization of learning, improves their time management skills and overall learning satisfaction. The results of the study deepen the provisions introduced byDehghani et al (2011), Lin et al (…”
supporting
confidence: 91%
“…Technologies were found to positively affect students' critical thinking, academic performance and career development, as they eliminate the dominance of explanatory-illustrative learning by substituting student-task-outcome-centred approaches to learning (Lupak et al, 2020). The technology-driven learning environment also provides individualisation of learning and increases student learning motivation (Giraldo-García et al, 2015;Gökçearslan et al, 2019;Lychuk et al, 2021;Nozhovnik & Shykhnenko, 2020;Schindler et al, 2017). Lychuk et al (2021) found that the above environment could be also organised as inquiry-based and learner-centred.…”
Section: Justification Of Procedures Presentation Of Arguments Self-r...mentioning
confidence: 99%
See 1 more Smart Citation
“…The flexible pedagogy that creates the theoretical framework for the study, relies on both students' freedom of choice concerning the learning strategies, pace, place, mode of learning and technology-mediated/enhanced learning (Gordon, 2014). It was also found that a student-customised approach to teaching languages, which is ensured by smart automated teaching, develops students' autonomy, enhances their cognitive processing speed, motivation, and language skills (Kurnaz et al, 2020;Santipolo, 2017;Shykhnenko & Nozhovnik, 2020). The use of technology in the smart learning instructional model prepares the students to act in the digital economy through adapting to its settings, sensing changes and impacts, and self-sustaining in a focused manner (Bonnaud, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%